INFÂNCIAS E FORMAÇÃO EM “O MENINO NITO” E “O MEU CRESPO É DE RAINHA”: DIVERSIDADES E EMANCIPAÇÃO. - Alessandra Rodrigues Cezário Gomes (2023)
This research brings reflections on how the children's literary book can be an important instrument in the search for representations of childhood and its ethnic, aesthetic and cultural identities for the education of children. In this context, the general objective is to analyze and explain children's literary works of Public Literature Policies aimed at the Early Years of Elementary Education (1st to 3rd Years) that bring the diversity delimited by the theme of childhood, as a generational category, in the face of ethnic and cultural relations. “racial” and gender issues, as a possibility of human and cultural formations for children. The research starts from a theoretical-methodological movement with Bibliographic Research and Documentary Research. To this end, public literature policies on the representativeness of black childhood in literary works and research on the themes of literature and diversity in official documents that guide the Early Years of Elementary Education were analyzed. We sought to describe the relationships between childhood and literature, reflecting on how these concepts can contribute to the construction of a positive identity for black and non-black children. In this way, comparisons of literature books by Monteiro Lobato and the racism present in the works were carried out. Finally, to think about didactic possibilities that address diversity in the classroom, we analyzed the literary works O Menino Nito, by Sonia Rosa, and Meu crespo é de Rainha, by bell hooks (with lowercase letters so as not to demonstrate superiority), which can be used as guiding examples to explore ethnic and “racial” relations and childhood and gender issues, focusing on the importance of children's literature for the human and emancipatory formations of children in the school context. The study is anchored in reflections of Critical Theory, specifically based on the authors Theodor Adorno and Max Horkheimer, and Cultural Studies, in the figure of Stuart Mcphail Hall. Antônio Candido de Mello e Souza, Marisa Philbert Lajolo, Regina Zilberman, Kabengele Munanga, Frantz Omar Fanon, Christian Muleka Mwewa and Joan Wallach Scott are also part of the theoretical framework. In addition to the theoretical contribution, official documents that guide the organization of the Early Years of Elementary Education were used, namely the Law of Guidelines and Bases of National Education (LDB); the National Curriculum Parameters (PCN); Law no. 11.645/2008, which amends Law n. 9,934/1996; the National Curriculum Guidelines (DNC) and the National Common Curriculum Base (BNCC). The central hypothesis resides in the idea that literature constitutes a relevant instrument in the search for childhood representations and their ethnic, aesthetic and cultural identities, being a possibility for training for diversity. We conclude that children's literary works that bring black characters as protagonists, and children as social actors, open the way for more fruitful, sensitive and human experiences in the light of a constructive process of bridges that break down with the racism present in Brazilian society. In this way, working with children's literary books in schools, which value the way of thinking about hair, bodies and the presence of black people in Brazil, can strengthen the self-esteem of black children and contribute to their identity formation in a positive way, providing the cultural formation towards humanization, whether for black or non-black children.